2022
DOI: 10.4236/aid.2022.123038
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Impact of COVID-19 on Healthcare Workers in Africa, Associated Factors and Coping Mechanisms: A Systematic Review

Abstract: Background: The coronavirus disease 2019 (COVID-19) is a public health problem that has caused harm to the mental health of healthcare workers. In Africa, the COVID-19 pandemic has led healthcare workers to experience mental health disorders such as anxiety, depression, stress, insomnia and burnout. This study aimed to review published studies on the effect of COVID-19 on the mental health of healthcare workers, associated factors and coping strategies that have been employed in Africa. Methods: This was a sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 48 publications
3
5
0
Order By: Relevance
“…The sentiments shared by the participants showed both rewarding and positive experiences, as well as many challenges that ranged from those embedded in the context of wider institutional difficulties to more personalised and patient-led experiences. Interestingly, the more positive experiences reported have similarly been identified by other studies conducted in LMICs (Htay et al 2021 ; Mudenda et al 2022 ) and in qualitative investigations of British frontline HCWs (Griffin & Riley 2022 ). Furthermore, a lot of adaptation and flexibility was required in workspaces to respond to the unpredictable and fluctuating working conditions.…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…The sentiments shared by the participants showed both rewarding and positive experiences, as well as many challenges that ranged from those embedded in the context of wider institutional difficulties to more personalised and patient-led experiences. Interestingly, the more positive experiences reported have similarly been identified by other studies conducted in LMICs (Htay et al 2021 ; Mudenda et al 2022 ) and in qualitative investigations of British frontline HCWs (Griffin & Riley 2022 ). Furthermore, a lot of adaptation and flexibility was required in workspaces to respond to the unpredictable and fluctuating working conditions.…”
Section: Resultssupporting
confidence: 72%
“…Despite coping mechanisms being identified as buffers for psychological support, the severe strain experienced resulted in feelings of helplessness, loss of hope and sometimes to social isolation. There is an overwhelming support for these findings in the international literature (Fournier et al 2022 ; Sultan et al 2022 ; Ali et al 2020 ; Newman et al 2022 ) and more specially in LMICs (Mudenda et al 2022 ; Naidoo et al 2020 ; Curran et al 2021 ; Dawood, Tomita & Ramlall, 2022 ; Watermeyer, Madonsela & Beukes 2023 ), emphasising the increased burden of mental health disease in HCWs globally. These findings reinforce the urgent call for increased psychological support for HCWs to mitigate severe physical and emotional strain.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Additionally, a survey among nurses working in a tertiary health facility in Kenya during COVID-19 reported depression, anxiety, insomnia, distress and burnout at 45.9, 48.2, 37.0, 28.8, and 47.9% ( 26 ). The risk factors for depression and anxiety were higher among females health workers, less than 30 years of age, not being married and those with less than 10 years of work experience ( 27 ). However, none of these studies reported the reliability or validity of the measures they employed to assess the mental health of the healthcare workers.…”
Section: Introductionmentioning
confidence: 99%
“…In one of the few cross-sectional survey studies focusing on LMICs, including South Africa, Kenya, Uganda, Tanzania and Zimbabwe, Htay and colleagues (2021) reported positive coping mechanisms, such as family support and positive thinking, as a method to counteract increased psychological and physical strain. A recent systematic review of the psychological impact of COVID-19 on HCWs in Africa demonstrated a similar pattern of increased mental health disease, with coping strategies of religion and social support used to buffer the negative psychological impact of the pandemic (Mudenda et al 2022). However, of the 18 studies included in this review, only two studies used qualitative interview methods to explore the experiences of psychological strain of HCWs in Ghana and Uganda.…”
Section: Introductionmentioning
confidence: 95%